Multiple levels of regulation of the interleukin-6 system in stroke - Weber, Daniela; Wiest, Tina; Hartmann, Marius; Farahmi, Maryam; Mansmann, Ulrich; Auffarth, Gerd U.; Grau, Armin J.; Green, Fiona R.; Grond-Ginsbach, Caspar; Schwaninger, Markus (Stroke, 2003)
Background and Purpose: Serum levels of the cytokine interleukin-6 (IL-6) rise markedly in stroke. IL-6 is a key regulator of inflammatory mechanisms that play an important part in stroke pathophysiology. The action of IL-6 is modified by its soluble receptor subunits sgp130 and sIL-6R. The purpose of this study was to investigate whether serum levels of the receptor subunits are changed after ischemic stroke and to define the role of genetic influences on IL-6 expression in acute stroke.Methods: In 48 patients with acute stroke and 48 age- and sex-matched control subjects, serum concentrations of IL-6, sgp130, and sIL-6R were measured by enzyme-linked immunosorbent assay. Furthermore, IL-6 promoter haplotypes comprising 4 different polymorphisms (−597G→A, −572G→C, −373A(n)T(n), −174G→C) were determined by DNA sequencing and allele-specific oligonucleotide polymerase chain reaction. The effect of the common haplotypes on IL-6 gene transcription was tested by transfecting reporter fusion genes in the astrocytelike cell line U373. Results: Whereas serum concentrations of IL-6 significantly rose (P<0.001), sgp130 levels were transiently reduced after stroke (P<0.05), and sIL-6R levels remained unchanged. IL-6 levels depended on the infarct size and the haplotype of the promoter region. The common haplotype A-G-8/12-C was associated with low IL-6 levels after stroke and a reduced induction of IL-6 transcription on stimulation with an adenosine analog in vitro. Conclusions: The data demonstrate genetic variation in the expression of IL-6 in stroke. Induction of the inflammatory response by IL-6 might be enhanced by a transient downregulation of the potential IL-6 antagonist sgp130.
Gesehen am 22.03.2021